GOVERNMENT BUDGET POLICY RELATED TO LOCKDOWN COVID19: A POLITICAL PRESSURE STUDY - Jamaluddin Majid; Mediaty Mediaty; Hamid Habbe; Harryanto Harryanto (Universitas Islam Negeri Alauddin Makassar, 2020)
This study aims to reveal more about the Government's budget policy regarding the handling of Covid-19 when viewed from a study of political pressure concerning compliance theory. This research is a type of qualitative research with a critical study approach, which is a way to understand the facts, events, situations, objects, people, and statements behind clear or direct meanings. This research's data collection method is a literature study or literature review, a process of collecting data and information through supporting data from national and international research journals, keeping books, newspapers, articles, and magazines. The data and information collected from data sources are then transcribed, reduced, analyzed, and then conclusions are drawn due to the research. The results show that the lockdown decision that has been issued by the Government will require a lot of budgets because the lockdown decision causes budget expenditure and economic expectations to increase. The budget prepared for the lockdown policy comes from non-priority expenditure budgets, such as official travel and other activities that cannot be carried out during the emergency period.Keywords: Budget, Government Policy, Covid-19 Lockdown, Political Pressure